2014
DOI: 10.5152/jtgga.2014.1111
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian cystectomy in endometriomas: Combined approach

Abstract: Endometrioma is one of the most frequent adnexal masses in the premenopausal population, but the recommended treatment is still a subject of debate. Medical therapy is inefficient and can not be recommended in the management of ovarian endometriomas. The general consensus is that ovarian endometriomas larger than 4 cm should be removed, both to reduce pain and to improve spontaneous conception rates. The removal of ovarian endometriomas can be difficult, as the capsule is often densely adherent. While the surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 31 publications
3
10
0
Order By: Relevance
“…Moreover, heating the tissue in order to stop bleeding during the surgery www.cajms.mn ovarian tissue and create another adhesion site. There are several reports demonstrated ovarian deficiency after stripping endometrioma from both ovaries [20]. In the present study, we have confirmed 2 cases of endometrioma recurrence in Group I patients who were administered progesterone after surgery, while there was not any cyst recurrence in the patients who had the same progesterone treatment before the surgery.…”
Section: Discussionsupporting
confidence: 83%
“…Moreover, heating the tissue in order to stop bleeding during the surgery www.cajms.mn ovarian tissue and create another adhesion site. There are several reports demonstrated ovarian deficiency after stripping endometrioma from both ovaries [20]. In the present study, we have confirmed 2 cases of endometrioma recurrence in Group I patients who were administered progesterone after surgery, while there was not any cyst recurrence in the patients who had the same progesterone treatment before the surgery.…”
Section: Discussionsupporting
confidence: 83%
“…Endometrioma drainage followed by ablation of the remaining cyst wall is an alternative procedure that significantly improve pelvic pain but recurrence still a major risk. Laparoscopic cystectomy is the first choice for conservative management of endometrioma [12, 14]. It carries the following benefits; decreases recurrence rates (it ranges from 9.6 to 45% after one surgery), increases spontaneous pregnancy rate (14–54%) & reduces pelvic pain [1517].…”
Section: Discussionmentioning
confidence: 99%
“…drainage has been controversial within the realm of subfertility, with conflicting ideas about whether drainage should be undertaken (32). The procedure can be easily performed under US guidance (either transabdominal or endovaginal depending on the most appropriate window) with minimal distress for the patient.…”
Section: Endometrioma Drainage-endometriomamentioning
confidence: 99%